GAS LIFT OPTIMIZATION AT K FIELD USING INTEGRATED PRODUCTION MODEL - SEPTOPANDUVIYATMO (NIM: 22214022), JUDGE
Gas lift is currently being used in K oil field as the artificial method. Gas lift requirement keep increasing due to lower producing reservoir pressure in K field. In line with that, gas production as gas lift source is also decreasing. With less gas production, to fulfil gas export commitment, gas lift portion need to be taken from export gas. Less gas lift volume can reduce oil production. This study is conducted to review how far the impact of less gas lift volume to K field oil production. To achieve the biggest cumulative production in constrained gas lift volume, gas lift allocation to Wells becomes important. There are several gas lift allocation optimization methods, some of them are equal slope method and sequential quadratic programming (SQP) method. This study will compare the cumulative production achieved if using gas lift allocation from equal slope method and SQP method. To know cumulative production that will be achieved until the end of PSC contract period, production prediction will be conducted from the end of production history time until the end of K field PSC contract period. Production prediction conducted in this study will integrate reservoir model, well model and production facilities model to accurately predict the production profile. Reservoir will be modelled with material balance, and it will be matched to production history so that the model will be able to predict reservoir pressure in the future. Matching will also be done at well model and production facilities model to the actual condition at the end of production history period. After all models are matched, production prediction simulation will be conducted with constrained gas lift volume, where simulator will allocate gas lift with equal slope method and SQP method. From simulation result, it can be seen that cumulative oil production of K field is affected by available total gas lift volume. Total gas lift volume constraint will decrease cumulative oil production at the end of PSC contract period with the government in 2028. Optimized gas lift allocation with SQP method will give better cumulative production compared with equal slope method. Gas lift allocation from SQP method can stabilize cumulative production if total gas lift is reduced down tol 4 MMscfd. If total gas lift less tan 4 MMscfd, then cumulative production will drop significantly. If there is no new well addition untuk the end of PSC contract period in 2028, then optimum total gas lift volume for K field is 4 MMscfd.